A dynamic simulation approach to soil salinity and sodicity in Konya plain of Turkey - Tunca, Mehmet Can. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2021., 2021)
Soil salinity and sodicity are twin problems potentially affecting soil fertility, farmers’ livelihoods and food security. Management and control of these problems, particularly on irrigated farmlands require knowledge and expertise crafted through appropriate models and experiments. The accumulation of salts on the soil profiles may occur through natural processes as well as by human actions, that are mostly related to poor agricultural and irrigation practices. Accumulation of salt in soil water impedes crop evapotranspiration, sodicity threatens the soil structure and degrades its hydraulic qualities. These problems are more pervasive in arid and semi-arid regions. Therefore, irrigation and agricultural practices are crucial in controlling these problems to avoid their undesired consequences. In this research, a dynamic simulation model is built to represent salinization and sodification in soil layers so as to test the long-term impact of alternative irrigation practices with respect to water quality, quantity and schedule, on soil fertility and farm yields. The model is developed based on the system dynamics methodology. Model parameter values are selected as representative of the field conditions of Konya Plain in Turkey, which is a semi-arid region partially experiencing soil salinization problems. This study is completed as a part of the TÜBİTAK-funded research project entitled, “Soil Salinity and Sodicity Management by Sustainable Irrigation Practices in Konya Plain”. Based on the scenario analyses performed in the research, irrigation water quality, irrigation method as well as crop rotations found to be important factors on soil salinization and sodification process in soil.
Keywords: Soils, Salts in.; Salinity and sodicity control -- Konya.; Irrigation -- Salinity and sodicity control -- Konya.